Tingkat Kepatuhan Penggunaan Obat Anti Tuberkulosis pada Pasien TB di Puskesmas Kota II, Kabupaten Mappi, Provinsi Papua Selatan - Grace Agnes Theresa Konowok; Khotimatul Khusna; Risma Sakti Pambudi (An-Najat, 2025)
Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis bacteria. Transmission of TB can be transmitted through droplets from people infected with tuberculosis bacilli. Tuberculosis is very much determined by the success of treatment in order to prevent all complications caused by tuberculosis. This study aims to determine the level of compliance with the use of anti-tuberculosis drugs in TB patients at the Kota II health center, Mappi Regency, South Papua Province. This study is a study using a descriptive observational method. The research instrument used in this study was the MMAS-8 (Modified MoriskyAdherence 8-Scale) questionnaire with 8 questions that have been tested for validation and reliability. Based on the results of the study, it was found that 25% of patients had a good level of compliance, 21.25% of patients had a sufficient level of compliance, and 53.75% had a low level of compliance. The researcher's conclusion shows that most of the respondents at the Kota II Community Health Center, Mappi Regency, South Papua Province had a low level of compliance with a presentation of 53.75%.